Outcome of intravesical doxorubicin installation in T1 non muscle invasive bladder cancer: experience from a tertiary hospital in Indonesia - Purnomo, Adhika Restanto; Zulfiqqar, Andy (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
In Indonesia, the proportion of non-muscle bladder cancer is low compared to other countries. Doxorubicin is currently one of options for adjuvant therapy for nonmuscle invasive bladder (NMIBC) that underwent transurethral resection of bladder tumor (TURBT). This study is aimed to evaluate the oncological outcome of doxorubicin intravesical. Eight consecutive T1 bladder patients who underwent TURBT with complete tumor resection, and received intravesical chemotherapy were enrolled in this study. All the clinical data were gathered retrospectively. One of eight patients did not respond to intravesical doxorubicin instillation. Patients were recorded with univocal, low grade and female patients. In conclusion, doxorubicin intravesical may be one of options. Despite a small number of samples were enrolled. This preliminary data showed promising results on intravesical doxorubicin instillation.